Development of a low-noise readout ASIC for Silicon Drift Detectors in high energy resolution X-ray spectrometry. (10th March 2017) - Atkin, E.; Levin, V.; Malankin, E.; Shumikhin, V.
Abstract: ASIC with a low-noise readout channel for Silicon Drift Detectors in high energy resolution X-ray spectrometry was designed and prototyped in the AMS 350 nm CMOS process via Europractice as a miniASIC. For the analog readout channel tests there was used the detector module SDD-10-130-PTW LTplus-ic (PNDetector GmbH). The measured energy resolution of this module with the designed readout channel: 200 eV (FWHM) at 55 Fe, -16 °C, 1 kcps and a peaking time of 8 μ s.